Surfactant induced increase in supercapacitor activity for nickel manganese oxide. (2023) - Rai, Aparna; Gyanprakash, Maurya; Kumar Rastogi, Chandresh; Mandal, Biswajit
Abstract: In this work, we are reporting the impact of ligand on the synthesis and electrochemical properties of nickel manganese oxide nanoparticles. We have prepared bare and cetyltrimethylammonium bromide (CTAB) coated nickel manganese oxide nanoparticles using the hydrothermal method at 120 °C. The comparative analysis of these two samples showed that the CTAB coated nickel manganese oxide (NMO) displays superior electrochemical characteristics due to the presence of a higher number of active Ni 2+ sites. Further, the galvanostatic charge and discharge (GCD) analysis for both bare and CTAB coated samples showed an increase in the discharging time with the number of GCD cycles. But the increased discharging time is higher for the CTAB coated nanoparticles which are attributed to an increase in the number of active Ni 2+ sites in this case. In addition, the physicochemical processes before and after cycling showed a decrease in the adsorption resistance, which is further attributed to an increase in activity with the cycling. Therefore, it is anticipated that the surfactant presents at the surface of the nano-catalyst and the cycling alters the morphology and number of active sites.